2016
DOI: 10.3762/bjoc.12.87
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective carbenoid insertion into C(sp3)–H bonds

Abstract: SummaryThe enantioselective carbenoid insertion into C(sp3)–H bonds is an important tool for the synthesis of complex molecules due to the high control of enantioselectivity in the formation of stereogenic centers. This paper presents a brief review of the early issues, related mechanistic studies and recent applications on this chemistry area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(12 citation statements)
references
References 73 publications
0
12
0
Order By: Relevance
“… 3 However, due to the high reactivity of the metal carbenoid species, occasionally lower selectivity is observed in stereoselective reactions. 4 In recent years, borane mediated activation of nitrogen containing compounds has become a popular area of research following the groundbreaking work from Braunschweig which demonstrated that borylene species can effectively bind and activate dinitrogen. 5 In particular, research groups have explored the activation of diazo compounds using triarylboranes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 3 However, due to the high reactivity of the metal carbenoid species, occasionally lower selectivity is observed in stereoselective reactions. 4 In recent years, borane mediated activation of nitrogen containing compounds has become a popular area of research following the groundbreaking work from Braunschweig which demonstrated that borylene species can effectively bind and activate dinitrogen. 5 In particular, research groups have explored the activation of diazo compounds using triarylboranes.…”
Section: Introductionmentioning
confidence: 99%
“…In general, the metal-carbenoid intermediates are reactive and therefore readily can undergo a range of organic reactions . However, due to the high reactivity of the metal carbenoid species, occasionally lower selectivity is observed in stereoselective reactions . In recent years, borane mediated activation of nitrogen containing compounds has become a popular area of research following the groundbreaking work from Braunschweig which demonstrated that borylene species can effectively bind and activate dinitrogen .…”
Section: Introductionmentioning
confidence: 99%
“…Undoubtedly, compounds 2a and 3a originated from cis and trans isomers of dilithiated 1 H -2,3-dihydroisoindole-1,3-diols, A cis/trans , formed by treatment of the parent (unsubstituted) hydroxylactams 1a with 2.3 equiv of the s -BuLi/TMEDA system (Figure ). One could suppose that with the elongation of rt reaction time these lithium alkoxides can undergo five-membered ring opening via tautomerization of their hemiketal moieties, proven by Tomooka et al, to form N,O -dilithiated γ-keto species B as classical carbenoids . The opposite reversible conversion, from open-chain ketones to cyclic alkoxy lithium salts, was reported by Epsztajn et al .…”
Section: Resultsmentioning
confidence: 99%
“…Enantioselective metal carbenoid C–H insertions are largely dominated by rhodium and copper catalysis; , however, over the last ten years, iridium chemistry has also brought an important contribution to this area. In 2009, Katsuki and co-workers introduced the first example of a catalytic enantioselective iridium carbenoid C–H insertion (Scheme ).…”
Section: Outer-sphere C–h Functionalizationmentioning
confidence: 99%